Bird ticks in Hungary reflect western, southern, eastern flyway connections and two genetic lineages of Ixodes frontalis and Haemaphysalis concinna. Issue 1 (December 2016) - Hornok, S.; Flaisz, B.; Takács, N.; Kontschán, J.; Csörgő, T.; Csipak, Á.; Jaksa, B.; Kováts, D.
Abstract Background Birds play an important role in short- and long-distance transportation of ticks and tick-borne pathogens. The aim of the present study was to provide comprehensive information on the species and genetic diversity of ixodid ticks transported by migratory and non-migratory bird species in Central Europe, and to evaluate relevant data in a geographical, as well as in an ecological context. Methods During a three year period (2012-2014), altogether 3339 ixodid ticks were collected from 1167 passerine birds (representatives of 47 species) at ringing stations in Hungary. These ticks were identified, and the tick-infestations of bird species were compared according to various traits. In addition, PCR and sequencing of part of the cytochrome oxidase subunit-I (COI) and 16S rDNA genes were performed from representatives of five tick species. Results The most abundant tick species found wereIxodes ricinus andHaemaphysalis concinna (with 2296 and 989 immature stages, respectively). In addition, 48I. frontalis (all stages), threeHyalomma rufipes nymphs, oneI. lividus and twoI. festai females were collected. The majority ofI. ricinus andI. frontalis specimens occurred on ground-feeding bird species, as contrasted toHa. concinna. Hy. rufipes showed the highest degree of sequence identity to an Ethiopian hybrid of the same tick species. Based on both COI and 16S rDNA gene analyses, two genetic lineages ofI. frontalis were recognized (with only 91.4 % identity in their partial COI gene). These were highly similar to South-Western European isolates of the same tick species. Phylogenetic analysis ofHa. concinna specimens collected from birds in Hungary also revealed two genetic lineages, one of which showed high (≥99 %) degree of 16S rDNA sequence identity to conspecific East Asian isolates. Conclusions Two genetic lineages ofI. frontalis andHa. concinna are transported by birds in Central Europe, which reflect a high degree of sequence identity to South-Western European and East Asian isolates of the same tick species, respectively. In addition, I. festai was collected for the first time in Hungary. These findings highlight the importance of western and eastern migratory connections by birds (in addition to the southern direction), which are also relevant to the epidemiology of tick-borne diseases.